PENYERAPAN TENAGA KERJA INDUSTRI RUMAH PANGGUNG DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT - Hizkia Daniel Assa; Oktavianus Porajouw ., Porajouw; Eyverson ., Ruauw (Sam Ratulangi University, 2021)
This research aims to analyze the labor absorption of the stilt house industry in Tombasian Atas Village, West Kawangkoan District. The research was conducted from February to May 2021. The data used in this study were primary data and secondary data and analyzed descriptively. The results showed that the stilt house industry in Tombasian Atas Village, Kawangkoan Barat District consisted of 3 (three) types, namely type 1 room, type 2 room, and type 3 room. The production of each type consists of 32 units per year for the one bedroom type, 40 units per year for the two bedroom type, and 10 units per year for the three bedroom type. The one-room stilt house type can absorb 51 workers, the two-room type absorbs 87 workers, and the three-room type absorbs 51 workers.